2011
DOI: 10.1007/s10533-011-9621-z
|View full text |Cite
|
Sign up to set email alerts
|

Absence of humic substance reduction by the acidophilic Fe(III)-reducing strain Acidiphilium SJH: implications for its Fe(III) reduction mechanism and for the stimulation of natural organohalogen formation

Abstract: A vast amount of volatile organohalogens (VOX) has natural origins. Both soils and sediments have been shown to release VOX, which are most likely produced via redox reactions between Fe(III) and quinones in the presence of halide anions, particularly at acidic pH. We tested whether acidophilic Fe(III)-reducers might indirectly stimulate natural VOX formation at acidic pH by providing reactive Fe and quinone species. However, it is unknown whether acidophilic Fe(III)-reducers can reduce humic acids (HA) or ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…To our knowledge, this statement still holds true and there is still no report of any neutrophilic Fe(III)-reducer that is unable to reduce HS. However, Emmerich and Kappler (2012) recently demonstrated that the acidophilic Fe(III)-reducer Acidiphilium SJH was neither able to reduce HS nor AQDS. In addition to Fe(III)-reducers, fermenting (Benz et al 1998), halorespiring, sulfate-reducing, and methanogenic microorganisms (Cervantes et al 2002) have been shown to be able to reduce HS.…”
Section: Electron Shuttling By Humics: a Two-step Processmentioning
confidence: 99%
“…To our knowledge, this statement still holds true and there is still no report of any neutrophilic Fe(III)-reducer that is unable to reduce HS. However, Emmerich and Kappler (2012) recently demonstrated that the acidophilic Fe(III)-reducer Acidiphilium SJH was neither able to reduce HS nor AQDS. In addition to Fe(III)-reducers, fermenting (Benz et al 1998), halorespiring, sulfate-reducing, and methanogenic microorganisms (Cervantes et al 2002) have been shown to be able to reduce HS.…”
Section: Electron Shuttling By Humics: a Two-step Processmentioning
confidence: 99%